Indian Banking: Changing Pattern of Employment and Issue of Employee's Efficiency in Global Era-Challenges and Opportunities - Uppal, R. K.; Kaur, Rimpi (Indian Journal of Marketing, 2007)
The paper analyzes the changes in employment pattern in banking sector in India in the post second banking sector reforms and analyzes the efficiency of the bank employees in the post liberalized and globalized era. The foreign banks account for insignificant proportion of total employment as compared to total banking sector employment. There is a structural shift in the employment in 2002 over the period 1999, where females are more concentrated in officer's jobs in foreign banks on the other side, in case of public sector banks females are concentrated in clerical jobs. The study reveals that female employment is the highest in foreign banks, nationalized banks are providing maximum employment. Region-wise employment is maximum in southern and western region. All the employees of foreign banks are more efficient as compare to other bank groups (efficiency is far better than other bank groups). The downsizing of employees in bank groups is highly and significantly correlated with the labour efficiency. At the end, paper finds some challenges for the public sector banks and highlights some suggestions that may be helpful for lower efficient bank groups to meet these challenges efficiently.